2021
DOI: 10.3389/fnana.2021.749390
|View full text |Cite
|
Sign up to set email alerts
|

The Stereological Analysis and Spatial Distribution of Neurons in the Human Subthalamic Nucleus

Abstract: The subthalamic nucleus (STN) is a small, ovoid structure, and an important site of deep brain stimulation (DBS) for the treatment of Parkinson’s disease. Although the STN is a clinically important structure, there are many unresolved issues with regard to it. These issues are especially related to the anatomical subdivision, neuronal phenotype, neuronal composition, and spatial distribution. In this study, we have examined the expression pattern of 8 neuronal markers [nNOS, NeuN, parvalbumin (PV), calbindin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 123 publications
1
7
0
Order By: Relevance
“…The literature search for studies of human STN revealed there are hardly any studies that analyzed the molecular phenotype or developmental origin of STN neurons. The majority of studies dealing with human STN analyzed expression patterns of calcium-binding proteins and neurotransmitter receptors in STN ( Lévesque and Parent, 2005 ; Zwirner et al, 2017 ; Wu et al, 2018 ; Alkemade et al, 2019 ), with only one study also analyzing TF expression ( Bokulić et al, 2021 ). However, all these studies analyzed the adult STN, so the data about TFs in the developing human STN is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search for studies of human STN revealed there are hardly any studies that analyzed the molecular phenotype or developmental origin of STN neurons. The majority of studies dealing with human STN analyzed expression patterns of calcium-binding proteins and neurotransmitter receptors in STN ( Lévesque and Parent, 2005 ; Zwirner et al, 2017 ; Wu et al, 2018 ; Alkemade et al, 2019 ), with only one study also analyzing TF expression ( Bokulić et al, 2021 ). However, all these studies analyzed the adult STN, so the data about TFs in the developing human STN is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, Nkx2-1 has now been acknowledged as a marker of pallidal neurons originating from the MGE, expressing parvalbumin, projecting to the STN, and having a high-frequency firing rate ( Abdi et al, 2015 ; Dodson et al, 2015 ). Interestingly, a recent study of the adult human STN described the expression of NKX2-1 in the STN, along with parvalbumin and calretinin ( Bokulić et al, 2021 ). As mentioned before, postmitotic neurons destined to populate the mouse STN downregulate Nkx2-1 , so the observed difference between human and mouse STN could indicate the existence of an additional neuronal subclass or a species-specific mechanism regulating its expression.…”
Section: Transcription Factors In the Developing And Adult Subthalami...mentioning
confidence: 99%
See 3 more Smart Citations